The use of gypsum mining by-product and lime on the engineering properties of compressed earth blocks (2014)
Disadvantages of compressed earth blocks are their poor mechanical properties and low resistance to water damage. Therefore, their use is vulnerable to deterioration and require care and maintenance, which depends on the degree of stabilization and compaction of the clay soil. Gypsum mining wastes and lime used as stabilization materials to improve the properties of these construction materials. The compressive and flexural strength, softening in water, drying shrinkage and unit weight determined. Strength values increased with both mining waste additions. Highest resistance against softening in water obtained with a 25% of mining waste. Drying shrinkage reduced with increasing mining waste content. Dry unit weight was not in the recommended standards. Results showed that gypsum mining wastes can be used as alternative materials to stabilize compressed earth blocks.